2008
DOI: 10.1371/journal.pone.0001472
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection and Adaptive Evolution of Leptin in the Ochotona Family Driven by the Cold Environmental Stress

Abstract: BackgroundEnvironmental stress can accelerate the evolutionary rate of specific stress-response proteins and create new functions specialized for different environments, enhancing an organism's fitness to stressful environments. Pikas (order Lagomorpha), endemic, non-hibernating mammals in the modern Holarctic Region, live in cold regions at either high altitudes or high latitudes and have a maximum distribution of species diversification confined to the Qinghai-Tibet Plateau. Variations in energy metabolism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 68 publications
(68 reference statements)
2
60
1
3
Order By: Relevance
“…However, the McDonald-Kreitman test showed no evidence of selection on the present Cytb gene of G. glis. It is possible that selection acted on another gene or genes more directly linked to hibernation or cold resistance, as was observed in Ochotona (Yang et al 2008). If so, this selection could have led to a European postglacial expansion from only a small number of cold-resistant animals, thereby resulting in the observed mitochondrial homogeneity.…”
Section: Discussionmentioning
confidence: 97%
“…However, the McDonald-Kreitman test showed no evidence of selection on the present Cytb gene of G. glis. It is possible that selection acted on another gene or genes more directly linked to hibernation or cold resistance, as was observed in Ochotona (Yang et al 2008). If so, this selection could have led to a European postglacial expansion from only a small number of cold-resistant animals, thereby resulting in the observed mitochondrial homogeneity.…”
Section: Discussionmentioning
confidence: 97%
“…The plateau pika, as a typical plateau mammal, has been extensively studied to understand this adaptation. HIF-1a (Li et al, 2008, Zhao et al, 2004 and leptin (Yang et al, 2006) expression, and leptin (Yang et al, 2008) and Hb (Yingzhong et al, 2007) (n = 10). Asterisks indicate significant differences compared with the altitude of 3200 m (**p < 0.01, ***p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou Le et al found that genetic distance and geographical distance of plateau pika population have no significant correlation (Zhou et al, 2007). Yang et al (2008) found that altitude has no significant effect on substitution rates of the gene-like leptin in pika. Here ten individuals of plateau pika from each site were used for mRNA analysis.…”
Section: Animal Tissue Preparationmentioning
confidence: 96%
See 1 more Smart Citation
“…The identity of the leptin protein in Xenopus to that of pufferfish, human, and tiger salamander (Ambystoma tigrinum) is 13%, 35%, and 60%, respectively [6,7,9]. Although, positive selections of leptins are revealed in several mammal lineages, for example, pikas (Ochotona curzoniae), Cetacea and Pinnipedia, and heterothermic bats [24][25][26], the conserved gene structure (three exons separated by two introns) and secondary and tertiary structures of leptins were found from teleosts to mammals [2,3,6,11,27,28]. Phylogeny reconstruction of vertebrate leptins showed that most vertebrates form distinct clades with topology consistent with the generally accepted vertebrate topology except that the relationships among teleosts remain inconsistent [2,11,29].…”
Section: Introductionmentioning
confidence: 99%